Osteoblastic cell behavior on nanostructured metal implants. (February 2008) - Guehennec, Laurent Le; Martin, Frantz; Lopez-Heredia, Marco-Antonio; Louarn, Guy; Amouriq, Yves; Cousty, Jacques; Layrolle, Pierre
Aims: Surface modifications at the nanometric scale may promote protein adsorption, cell adhesion and thus favor the osseointegration of metal implants. The behavior of osteoblastic cells was studied on mirror-polished (Smooth-SS) and nanostructured (Nano-SS) stainless steel surfaces.Materials & methods: The nanostructuration was obtained by anodization. The surfaces were characterized by scanning electron, atomic force microscopy (AFM) and X-ray photoelectron specytoscopy. Osteoblastic cells were cultured on these surfaces.Results & discussion: AFM showed a regular array of pores on the Nano-SS. Osteoblastic cells spread more rapidly on Nano-SS surfaces than on Smooth-SS surfaces. Cell viability was similar on Smooth-SS and Nano-SS. Alkaline phosphatase activity increased with culture time whatever the substrate but was better enhanced at 21 days on the Nano-SS than on the Smooth-SS.Conclusion: This study shows that the nanostructuration of metal implants may improve the adhesion and differentiation of osteoblastic cells.